Methanolic extract of Citrullus Lanatus seeds abates testicular degeneration and dose-dependently modulates testicular function in hyperlipidemic male Wistar rats. (Nigerian Journal of Physiological Sciences, 2021)
Hyperlipidemia is emerging as an important cause of adverse health outcomes including cardiovascular complications, obesity, metabolic disorders, and infertility. A total of twenty-five (25) male albino Wistar rats were divided into five groups (n=5): Normal control, Hyperlipidemic control group which was administered (intra-peritoneal) with 0.2ml/10g body weight of egg yolk and then terminated after twenty-four (24) hours, Hyperlipidemic non-treated group which were administered with 0.2ml/10g body weight of egg yolk and were left throughout the treatment period. Hyperlipidemic low-dose treated group (administered 0.2ml/10g body weight of egg yolk, 800mg/kg body weight of methanolic extract of Citrullus lanatus seed-MECLS), and Hyperlipidemic high-dose treated group (administered 0.2ml/10g body weight of egg yolk, and 1600mg/kg body weight of MECLS).  No significant change was observed in testosterone levels and sperm count across all groups. However, a statistically significant increase (P